Engineering Active Interfaces on the Surface of Porous Single-Crystalline TiO2 Monoliths for Enhanced Catalytic Activity and Stability - Huang Lin; Cong Luo; Fangyuan Cheng; Kui Xie (Research)
The engineering design and construction of active interfaces represents a promising approach amidst numerous initiatives aimed at augmenting catalytic activity. Herein, we present a novel approach to incorporate interconnected pores within bulk single crystals for the synthesis of macroscopic porous single-crystalline rutile titanium oxide (R-TiO2). The porous single crystal (PSC) R-TiO2 couples a nanocrystalline framework as the solid phase with pores as the fluid phase within its structure, providing unique advantages in localized structure construction and in the field of catalysis. We successfully construct well-defined Ni cluster/TiO2 active interfaces by directly confining Ni clusters on the continuous lattice surface of PSC R-TiO2. We confirm that the lattice oxygen connected to the Ni clusters exhibits exceptional activation capability at temperatures close to room temperature compared to the pure phase PSC R-TiO2 monoliths. The PSC Ni/TiO2 catalyst demonstrates complete CO oxidation and stable catalytic performance during continuous operation in air at ~80 °C for 200 h.